2017
DOI: 10.1017/ice.2017.226
|View full text |Cite
|
Sign up to set email alerts
|

No-Touch Disinfection Methods to Decrease Multidrug-Resistant Organism Infections: A Systematic Review and Meta-analysis

Abstract: BACKGROUND Recent studies have shown that using no-touch disinfection technologies (ie, ultraviolet light [UVL] or hydrogen peroxide vapor [HPV] systems) can limit the transmission of nosocomial pathogens and prevent healthcare-associated infections (HAIs). To investigate these findings further, we performed a systematic literature review and meta-analysis on the impact of no-touch disinfection methods to decrease HAIs. METHODS We searched PubMed, CINAHL, CDSR, DARE and EMBASE through April 2017 for studies ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 47 publications
1
70
0
4
Order By: Relevance
“…PX‐UV was evaluated in clinical hematologic and bone marrow units, and it provided an overall reduction of 90% in total aerobic colony counts compared with a 76% reduction with manual cleaning . At MD Anderson, we observed that PX‐UV light was noninferior compared with bleach for decreasing C. difficile spores from patients' rooms, as described in a recent systematic review of over 20 studies in which the use of automated UV‐C light devices achieved a significant reduction in C. difficile infections (RR, 0.64; 95% CI, 0.49‐0.84) and VRE infections (RR, 0.42; 95% CI, 0.28‐0.65); however, there was no significant impact on the rates of infection with MRSA or MDR‐GNB . In a recent cluster‐randomized, multicenter, crossover study, there was a decrease in the target organisms (mainly C. difficile ) in exposed patients after adding UV‐C light (using mercury devices) to standard cleaning, but this decreased rate was not associated with a change in the incidence of C. difficile infection .…”
Section: Environmental Cleaningmentioning
confidence: 53%
“…PX‐UV was evaluated in clinical hematologic and bone marrow units, and it provided an overall reduction of 90% in total aerobic colony counts compared with a 76% reduction with manual cleaning . At MD Anderson, we observed that PX‐UV light was noninferior compared with bleach for decreasing C. difficile spores from patients' rooms, as described in a recent systematic review of over 20 studies in which the use of automated UV‐C light devices achieved a significant reduction in C. difficile infections (RR, 0.64; 95% CI, 0.49‐0.84) and VRE infections (RR, 0.42; 95% CI, 0.28‐0.65); however, there was no significant impact on the rates of infection with MRSA or MDR‐GNB . In a recent cluster‐randomized, multicenter, crossover study, there was a decrease in the target organisms (mainly C. difficile ) in exposed patients after adding UV‐C light (using mercury devices) to standard cleaning, but this decreased rate was not associated with a change in the incidence of C. difficile infection .…”
Section: Environmental Cleaningmentioning
confidence: 53%
“…Previous studies evaluating environmental disinfection were designed to decontaminate rooms of patients known to be infected or colonized with MDROs. [2][3][4] By evaluating a post-MERS outbreak environmental disinfection, we suggest that nontargeted, partial environmental disinfection also results in reduction of overall VRE burden. This finding supports implementation of environmental cleaning measures as a routine practice, especially in hematology or transplant wards where VRE would cause clinical infections.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental disinfection using sodium hypochlorite or hydrogen peroxide vapor has demonstrated its effect on reducing multidrug-resistant organisms (MDROs) in several studies, especially for high-risk wards or outbreak control. [1][2][3][4] However, because such disinfection processes require evacuation of patient rooms, the effects of environmental disinfection not targeted for MDRO-contaminated spaces have not yet been evaluated. After a hospital-associated outbreak of Middle East respiratory syndrome (MERS), we conducted environmental disinfection of patient rooms where confirmed patients with MERS stayed.…”
mentioning
confidence: 99%
“…The application of non-manual vehicle disinfection lowers the possibility of human errors linked to traditional cleaning methods and offers the prospect of more effective elimination of pathogens, thereby decreasing infection transmission [26]. However, at present definitive evidence is lacking to demonstrate the clinical effectiveness of non-touch or automated disinfection procedures, including those utilize steam cleaning, hydrogen peroxide or ultraviolet light irradiation, to eradicate or suppress infection rates in ambulances [27,28].…”
Section: Cleaning and Disinfection Protocols For Emergency Medical Vementioning
confidence: 99%